Rituals and myths at the death ceremony of the Toraja People: Studies on the Rambu Solo Ceremony - Lambok Hermanto Sihombing (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2022)
Rambu Solo is a well-known ritual or traditional ceremony from the Toraja tribe in South Sulawesi. Rambu Solo is tribute to the funeral of the Toraja people who died. With lots of culture and tradition in Indonesia, the ritual of Rambu Solo is distinguished as being very sacred, scary and also expensive. The aim of this study is to find out how the Toraja tribe is still preserving the sacred tradition of Rambu Solo in this modern era. The author utilized the qualitative approach to analyze the rituals and myths at the death ceremony of the Toraja people. In order to help the author doing the analysis, Cultural Identity theory from Stuart Hall is applied in this study. To assist the author with the analysis, the author took the data from YouTube and other literary works related to this ritual. The result indicates that even though this funeral ceremony is sacred, scary, and costly, the Toraja people keeps preserving their tradition from generation to generation.    Rambu Solo adalah sebuah ritual atau upacara adat yang terkenal dari suku Toraja di Sulawesi Selatan. Rambu Solo merupakan penghormatan terhadap pemakaman orang Toraja yang meninggal. Dengan banyaknya budaya dan tradisi di Indonesia, ritual Rambu Solo berbeda karena ritual ini sangat sakral, menakutkan dan juga mahal. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana suku Toraja masih melestarikan tradisi sakral Rambu Solo di era modern ini. Penulis menggunakan pendekatan kualitatif untuk menganalisis ritual dan mitos pada upacara kematian orang Toraja. Untuk membantu penulis melakukan analisis, teori Identitas Budaya dari Stuart Hall diterapkan dalam penelitian ini. Penulis mengambil data dari YouTube dan karya sastra lainnya yang terkait dengan ritual Rambu Solo. Hasil penelitian ini menunjukkan bahwa meskipun upacara pemakaman ini sacral, menakutkan dan mengeluarkan banyak biaya, masyarakat Toraja tetap melestarikan tradisi mereka dari generasi ke generasi.